IAPT: help or hindrance to general practice? - Manning, Chris (London J Prim Care (Abingdon), 2009)
KEY MESSAGES: IAPT needs to improve how it expresses itself to the outside world. Commissioning should be concerned with activities that develop and sustain trusting and therapeutic relationships as well as treat illnesses. Polyclinics should enable local people to collaborate and themselves improve their collective mental health. IAPT should enhance and not destabilise existing good practice. WHY THIS MATTERS TO ME: For years I have been working to improve mental health provision in primary care. IAPT is potentially a powerful device to make a quantum leap forward, leaving behind poor primary care practice that medicalises appropriate distress and responses to life, and building from the best.